Pelatihan Digital Marketing untuk guru dalam mendukung school branding pada SDI Plus Darul Ulum Limo, Depok. - Tri; Erly Krisnanik; Anita Muliawati; Tjahjanto Tjahjanto; Bambang Triwahyono (Jurnal Pengabdian kepada Masyarakat Bidang Ilmu Komputer, 2025)
Increasingly fierce competition among educational institutions demands that schools have strong digital visibility. This study aims to describe the implementation of digital marketing strategies through intensive training for teachers to strengthen school branding at SDI Plus Darul Ulum Limo, Depok. The method used was practice-based training and mentoring (action learning) attended by 30 teachers. Data were collected through pre-test and post-test instruments, as well as observations of the school's social media engagement rate. The results showed a significant increase in teacher competency with an N-Gain score of 0.71 (High category). Teachers were able to produce creative content based on school values, which resulted in an increase in the school's official social media engagement rate by up to 15%. This proves that teacher involvement in digital marketing strategies is effective in building an authentic and communicative school image for the wider community.